2021
DOI: 10.5455/javar.2021.h551
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal parasites in three groups of domestic poultry managed under backyard system in the Savanna subregion, Department of Sucre, Colombia

Abstract: Objective: To identify the prevalence of gastrointestinal parasites that affect the backyard poultry system in the Savanna region, Department of Sucre, Colombia. Materials and Methods: Fecal samples were collected from 860 native birds, both hens ( Gallus domesticus ), ducks ( Anas platyrhynchos domesticus ), and turkeys ( Meleagris gallopavo ), regardless of age and sex. Samples were proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(19 reference statements)
1
0
0
Order By: Relevance
“…( Shifaw et al, 2021 ). In a study conducted on 64 backyard poultry farms in the state of Alabama, a prevalence of 20.3% of Ascaridia galli and Heterakis gallinarum and 26.6% of Capillaria was observed ( Carrisosa et al, 2021 ), similar to that reported in a study in Colombia, where birds were mainly affected by Capillaria (45.6%) ( Montes-Vergara et al, 2021 ) or in West Indies where they found highly prevalence of Capillaria spp. (63%), followed by Heterakis gallinarum (36%) and Ascaridia galli (12%) ( Bolfa et al, 2019 ).…”
Section: Introductionsupporting
confidence: 82%
“…( Shifaw et al, 2021 ). In a study conducted on 64 backyard poultry farms in the state of Alabama, a prevalence of 20.3% of Ascaridia galli and Heterakis gallinarum and 26.6% of Capillaria was observed ( Carrisosa et al, 2021 ), similar to that reported in a study in Colombia, where birds were mainly affected by Capillaria (45.6%) ( Montes-Vergara et al, 2021 ) or in West Indies where they found highly prevalence of Capillaria spp. (63%), followed by Heterakis gallinarum (36%) and Ascaridia galli (12%) ( Bolfa et al, 2019 ).…”
Section: Introductionsupporting
confidence: 82%